Revitalizing Speaking Fluency through Task-Based Language Teaching: Addressing Post-Pandemic Communicative Gaps in EFL Classrooms - Jannah, Khofifah Indah Baitul; Razaq, Siti Ulfya Syahara; Hafizudin, Hafizudin (Bulletin of Scientific Reseach in English Education, 2025)
Speaking skills are an important component of English as a foreign language (EFL) acquisition, yet they are one of the most affected by online learning during the COVID-19 pandemic. The lack of direct verbal interaction and the low intensity of oral practice lead to gaps in students' speaking fluency. In this context, the Task-Based Language Teaching (TBLT) approach offers a strategy oriented towards developing communication skills through meaningful tasks. This study aims to explore the impact of implementing TBLT on improving EFL students' speaking fluency in post-pandemic secondary schools. This study used a quasi-experimental approach with a pre-test and post-test control group design. The sample consisted of 60 grade XI students in one of the public high schools in Indonesia, who were divided into an experimental group and a control group. Data were collected through oral tests and analyzed using paired sample t-test and independent sample t-test. The results showed that there was a significant increase in the level of speaking fluency of students who took part in learning with the TBLT approach compared to the control group. The task-based activities proved to improve students' fluency, fluency, and confidence in speaking. The findings recommend the wider application of TBLT as a strategic approach in addressing the impact of online learning on EFL students' speaking ability.